2007
DOI: 10.2753/jec1086-4415110401
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Technology Fit: Effects of Cultural Characteristics on the Post-Adoption Beliefs of Mobile Internet Users

Abstract: Little is known about how culture affects users' perceptions and beliefs after they have adopted an information technology (IT). This study constructed and verified a research model, based on interaction theory and the cultural lens model, that focuses on the relationship between users' cultural profiles and post-adoption beliefs in the context of the mobile Internet. The results of large-scale on-line surveys in Korea, Hong Kong, and Taiwan indicate that four cultural factors-uncertainty avoidance, individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(149 citation statements)
references
References 67 publications
5
141
1
2
Order By: Relevance
“…Various studies in the literature emphasize that there are differences between countries with regards to the acceptance and use of different technologies (Sun & Zhang, 2006;Lee et al, 2007;Al-Gahtani et al, 2007;Im et al, 2011). The hypotheses put forward in this study concerning the differences between countries can be listed as follows:…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies in the literature emphasize that there are differences between countries with regards to the acceptance and use of different technologies (Sun & Zhang, 2006;Lee et al, 2007;Al-Gahtani et al, 2007;Im et al, 2011). The hypotheses put forward in this study concerning the differences between countries can be listed as follows:…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are numerous studies focusing on the acceptance and use of information technologies (Fishbein & Ajzen, 1975;Davis, Bagozzi, & Warshaw, 1989;Taylor & Todd, 1995;Venkatesh, Morris, Davis, & Davis, 2003;Sun & Zhang, 2006;AlGahtani, Hubona, & Wang, 2007;Lee, Choi, Kim, & Hong, 2007;Im, Hong, & Kang, 2011). These studies indicate that there are various important factors that affect the acceptance and use of information technologies by individuals belonging to different countries and cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has analyzed overall satisfaction with online channel services and concluded that customers' overall satisfaction with a service provider is determined by the service quality provided through the online channel, as well as through the traditional channel [28]. Specifically with regard to continuous intention to use mobile internet services, prior studies have established that user satisfaction consistently results in high continuance usage intention [26] and that continuance usage intention of mobile internet users will grow stronger as their overall satisfaction with the mobile internet service increases [20]. It was therefore hypothesized that:…”
Section: H3: Usage Of An M-banking Application Is Positively Associatmentioning
confidence: 99%
“…In their paper examining the success in Japan of iMode, a mobile internet system, Barnes and Huff (2003) thetrams.co.uk) Lee et al (2007) further examines the uptake of mobile internet through a post adoption study in the Far East. They attribute Korean, Hong Kong and Taiwanese attitudes to IT technology as being due to the "cultural lens" through which those cultures view it.…”
Section: Challenge 1: Cultural Biasmentioning
confidence: 99%